Investigation into moisture desorption in concrete constructions - Arūnas Aleksandras Navickas (Engineering Structures and Technologies, 2011)
The article investigates the moisture desorption of concrete constructions. Three concrete mixtures with different V/C ratio were tested. In one of the mixtures, a plasticizer was used. The test revealed changes in bulk humidity and weight. Specimens were dried in a natural environment after equilibrium moisture in a drying oven was reached. In the beginning of the test, the volume humidity of specimens with D1 composition varied in the range of 2.3 %. At the end of measuring, when constant weight was reached, moisture range decreased up to 0.3 %. When starting the test, the dispersion of the results of bulk humidity of specimens with D2 and D3 composition (Table 1) at an average was 1.3 % and at the end of the test it made 0.2 %. In the specimens of D2 and D3 composition, the results of the measurement of bulk humidity were scattered less. Also, an effect of concrete structure on the desorption process, rating pore and capillary structure in concrete and theirshape has been evaluated. When a constant weight of specimens was reached, the specimen were cut into two parts about 2cm from the plane where moisture had been measured. For subsequent tests, the top cut part was used, because the depthof measuring moisture was about 2 cm. Visual examination displayed that minimum moisture was in the points with large aggregates near the surface. After a comparison of the specimens it can be affirmed that moisture content is less in the points where the structure of concrete is more massive and less capillaries can be seen.